Concept of Kshara and Its Sources in Ayurveda- A Critical Review: LifeScience-Ayurveda - Soni, Shreya; Asutkar, Sheetal; Kumar Upadhyay, Sandeep; Pundlik Kadav, Amar (International Journal of Life Science and Pharma Research, 2023)
Kshara’ is related to ‘Paka’ (preparation) and ‘vidhi’ (application). Because of its superiority among the sharper andauxiliary instruments, caustic alkali performs excision, incision, and scarification, alleviating three doshas and being used forspecific functions. Among the para-surgical measures, all three- Agni (cauterization), Kshara (caustic alkali), and Jalauka (leeches)are important. Still, kshara is the chief because operations excision, incision, etc., cannot be performed by Agni and Jalauka. It isalso applied for specific purposes, such as in Arsha caused by Pitta. This article will be essential in containing from the smallest todeepest knowledge of Akshara, which is available in classics & articles in scattered forms. This study intends to gather allinformation related to Kshara and elaborate on their properties as mentioned in classics, especially in Sushruta Samhita andRasashashtra. The method followed here thoroughly analyzes Sushruta Samhita, its commentaries, and various research articlesthat surfed online. It is found that Sushruta Samhita explains full information regarding Kshara, types, indications, andcontraindications.In contrast, certain dravya, which are not explained as Kshara but possess Kshara properties, are also discussed.The research provides thorough literature & critical review of Kshara, its sources, and their properties which can benefit manydiseases in terms of application in different forms. In this study, the aim is to gather information about Kshara mentioned inclassics and articles. This study aims to collect information about Kshara from traditional and scholarly sources.